PENYUSUNAN PRODUK HUKUM SEBAGAI KEWENANGAN PEMERINTAHAN NAGARI DI KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Sahnan Sahuri Siregar; Otong Rosadi; Darmini Roza (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
This community service activity was carried out on Wednesday, August 21, 2019 with the first aim, to find out and analyse the background knowledge and experience of the nagari device to influence knowledge and abilities (expertise) in the preparation of Nagari Legal Products. Second, to find out and analyse how to increase the capacity of knowledge and abilities (expertise) of the Nagari Tool kit in preparing Nagari Legal Products? Third, to find out and analyse the right strategy to increase the capacity of the nagari government apparatus and members of Bamus Nagari so that they are able to draft a Nagari Regulation that is based on the needs of the nagari community. Community service activities in the form of training are carried out using lecture, question-answer, deepening and training methods. The lecture method is used as a preliminary briefing on several theories, concepts, and laws and regulations relating to nagari legal products, as well as to increase the motivation of nagari devices in the preparation of nagari legal products. While the question-and-answer method provides an opportunity for participants to discuss obstacles that arise during their practice and experience in arranging nagari legal products. The training method is used to practice the formulation of nagari regulations. Based on the activities that have been carried out, it can be concluded that almost all the training participants were very enthusiastic in participating in the training that was held with an indication that the active participants were discussing, the nagari as participants were present from the beginning of the opening until the end of the opening. After the training ended, he was able to understand and practice well all the material delivered during the service activities. The obstacle that arises is the limited space in the Bayang Sub district area, so that the place is done in the Nagari Office Hall which is too large and not soundproof so that the implementation of activities must use a loudspeaker.